Electroporation assisted delivery of Roussin salt porphyrin-based conjugated carbon nanoparticles for sono–X-ray–photodynamic prostate cancer in vitro and in vivo treatment - Samir Ali Abd El-Kaream; Abed Elrahman Ahmad Mohamad; Sohier Mahmoud El-Kholey; Samia Abd El-Moniem Ebied (Cancer Nanotechnology)
Abstract Background In the realm of cancer treatment, sono–X-ray–photodynamic therapy (SXPDT) has garnered significant interest as a novel therapeutic approach. The essential part of SXPDT is the sensitizer, which under X-ray photon and ultrasound sono-irradiation may transform sono and photo-energy into cytotoxic molecules. Photon absorption, targeting, penetration, and oxygen dependence remain challenges in sono–X-ray–photosensitizer (SXPs) design. Rapid advancements in material science have prompted the creation of several SXPs that create cytotoxic species with great selectivity, safety, and noninvasiveness for the treatment of tumors. The current study aims to provide an advanced method of activated cancer treatment by using electroporation to assist the delivery of Roussin salts porphyrin-based conjugated carbon nanoparticles (EP@RRBP-CNP) for the sono–X-ray–photodynamic prostate cancer (PCa) in vivo and in vitro treatment. Materials and methods Human PCa cells (DU-145) were used in the in vitro study, and the in vivo application groups of the study protocol were Swiss albino mice treated with N-methyl-N-nitrosourea (MNU) / testosterone only; they were not given any treatment to induce PCa. The study treatment protocol started only after PCa induction, and involved daily administration of EP@RRBP-CNP as SXPDT sensitizer whether or not to be exposed to photo–(X-ray) or sono–(US) or a combination of them for 3 min for a period of 2 weeks. Results Indicated that CNP is a useful RRBP delivery mechanism that targets PCa cells directly. Furthermore, EP@RRBP-CNP is a promising SXPS that, when used in conjunction with SXPDT, can be very effective in in vitro treating PCa-DU-145 (in a dose-dependent manner cell viability declined, an increase in the cells population during the G0/G1-phase indicates that the cell cycle was arrested, and an increase in cell population in the Pre-G, autophagic cell death, as well as necrosis and early and late apoptosis, indicate that cell death was induced) and MNU/testosterone-PCa-induced mice in vivo (induced antiproliferative genes, p53, Bax, TNFalpha, caspase 3,9, repressed antiangiogenic and antiapoptotic genes, VEGF and Bcl2, respectively), successfully slowing the growth of tumors and even killing cancer cells, as well as lowering oxidative stress (MDA), improving the functions of the kidneys (urea, creatinine), liver (ALT, AST), and antioxidants (GPx, GPx, GST, CAT, GSH, TAC). SXPDT, the X-ray photo- or sono-chemical RRBP activation mechanism, and the antioxidant capacity of non-activated RRBP can all be linked to this process. Conclusion On the bases of the findings, EP@RRBP-CNP shows a great promise as a novel, efficient selective delivery system for localized SXPDT-activated prostate cancer treatment.